Penyelesaian Sengketa Perbankan Syariah Melalui Litigasi Menurut Peraturan Perundang-Undangan Di Indonesia - Heni Marlina; Luil Maknun (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2022)
Banking has a function as an intermediary institution, namely utilizing funds from people who have excess funds and channeling them back to people in need in the form of financing facilities. This means that banking has a vital role in the economic sector, especially in regulating the circulation of money in society. Settlement of sharia banking disputes through non-litigation can be done through arbitration and alternative settlements, which consist of consultation, negotiation, mediation, conciliation, or experts as regulated in Law Number 30 of 1999 concerning Arbitration and Alternative Disputes. In arbitration, customers and Islamic banks are given the right to choose the legal material to be applied as stipulated in Article 56 paragraph (2) of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution